Kreativitas Guru dalam Membuat dan Memanfaatkan Alat Peraga PAI - Poby Noprian (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2022)
Data Collection Methods used in this study are: 1) Observation. 2) Interview. 3) Documentation. The results of the research at the Azzahroh City of Pagar Alam under the title of the thesis Study of Teacher Creativity Analysis in Making and Utilizing the PAI Teaching Aids at the Azzahroh City of the Pagar Alam City are as follows: 1) The teaching and learning activities of PAI at the Azzahro City of Pagar Alam are directed towards the realization of a complete learning process (mastery learning). While the learning strategy is directed to be able to stimulate active and creative students according to their respective talents, interests and abilities by paying attention to harmony and balance. 2) The creativity of PAI teachers in Mi Azzahro, Pagar Alam City, in making and utilizing teaching aids in the learning process can foster faith and faith through giving, fertilizing, and developing knowledge, appreciation, practice, habituation, habituation, and experience of students. 3) In Mi Azzahro City of Pagar Alam there are employees who help prepare and make props which are the creative team of PSB.